Review Article: A. RHOBY & N. ZAGKLAS (eds.), Middle and Late Byzantine Poetry: Texts and Contexts [ΒΥΖΑΝΤΙΟΣ. Studies in Byzantine History and Civilization 14], Turnhout 2018 - CHRYSSOGELOS, Konstantinos (Byzantina Symmeikta, 2021)
Review Article: A. RHOBY & N. ZAGKLAS (eds.), Middle and Late Byzantine Poetry: Texts and Contexts [ΒΥΖΑΝΤΙΟS. Studies in Byzantine History and Civilization 14], Turnhout 2018